Bacterial meningitis: new therapeutic approaches. Issue 10 (October 2013) - Nau, Roland; Djukic, Marija; Spreer, Annette; Eiffert, Helmut
Bacterial meningitis remains a disease with high mortality and long-term morbidity. Outcome critically depends on the rapid initiation of effective antibiotic therapy. Since a further increase of the incidence of pathogens resistant to antibacterials can be expected both in community-acquired and nosocomial bacterial meningitis, the choice of an optimum initial empirical antibiotic regimen will gain significance. In this context, the use of antibiotics which are bactericidal but do not lyse bacteria, may emerge as a therapeutic option. Conversely, the role of corticosteroids, which decrease the entry of hydrophilic antibacterials into the cerebrospinal fluid, as adjunctive therapy will probably decline as a consequence of the increasing antibiotic resistance of bacteria causing meningitis. Consequent vaccination of all children at present is the most efficient manner to reduce disease burden.